Transient Receptor Potential Ankyrin 1 Channel Expression on Peripheral Blood Leukocytes from Rheumatoid Arthritic Patients and Correlation with Pain and Disability - Pereira, Ione; Mendes, Saulo J. F.; Pereira, Domingos M. S.; Muniz, Thayanne F.; Colares, Valderlane L. P.; Monteiro, Cinara R. A. V.; Martins, Mahiba M. R. de S.; Grisotto, Marcos A. G.; Monteiro-Neto, Valério; Monteiro, Sílvio G.; Calixto, João B.; Brain, Susan D.; et al. (Frontiers in Pharmacology, 2017)
Patients with rheumatoid arthritis (RA) suffer from pain and joint disability. The transient receptor potential ankyrin 1 (TRPA1) channel expressed on sensory neurones and non-neuronal cells mediates pain transduction and inflammation and it has been implicated in RA. However, there is little information on the contribution of TRPA1 for human disease. Here, we investigated the expression of TRPA1 on peripheral blood leukocytes and the circulating levels of its endogenous activators 4-hydroxynonenal (4-HNE) and hydrogen peroxide (H2O2) in RA patients treated or not with the anti-rheumatic leflunomide (LFN) or the anti-TNFα adalimumab (ADA). We also assessed whether TRPA1 expression correlates with joint pain and disability, in addition to the immune changes in RA. TRPA1 expression on peripheral blood leukocytes correlated with pain severity and disability. TRPA1 levels on these cells were associated with the numbers of polymorphonuclear and the activation of CD14+ cells. No correlations were found between the lymphocyte population and TRPA1 expression, pain or disability. Patients recently diagnosed with RA expressed increased levels of TRPA1 on their leukocytes whilst treatment with either LFN or ADA down-regulated this receptor probably by reducing the numbers of polymorphonuclears and the activation of CD14+ cells. We suggest that the activation levels of CD14+ cells, the numbers of PMNs in the peripheral blood and the expression of TRPA1 on peripheral blood leukocytes correlate with RA progression, affecting joint pain sensitivity and loss of function.